Toxicity evaluation of wastewater collected at different treatment stages from a pharmaceutical industrial park wastewater treatment plant. (September 2016) - Ma, Ke; Qin, Zhe; Zhao, Zhongqing; Zhao, Chunxia; Liang, Shuxuan
Abstract: The toxicity of water-receiving bodies, the effluent and other treatment stages in wastewater treatment plants has recently been of interest to the public due to the lack of a regulated toxicity-based index for wastewater discharge in China. This study aimed to evaluate the conventional pollution parameters and toxicities of wastewaters collected at different treatment stages from a pharmaceutical industrial park wastewater treatment plant through dehydrogenase activity (DHA) and bioluminescent bacteria ( Vibrio qinghaiensis ) tests. The results of an analysis of conventional parameters indicated that the total suspended solids (TSS), chemical oxygen demand (COD), total nitrogen (TN), ammonia nitrogen (NH3 N), and total phosphorus (TP) were largely removed after various treatments. However, the TN, NH3 N and COD still exceeded the regulated standards. The tested pharmaceutical park effluents were mainly polluted with organic pollutants and nitrogenous. The toxicity test results indicated that the toxicities could be markedly reduced after treatment, with the toxicities of two out of the six effluent samples at different treatment stages being greater than the influent toxicity. Spearman's rank correlation coefficients indicated a significantly positive correlation between the toxicity values obtained using the DHA and Vibrio qinghaiensis tests. Compared with the DHA measurement, the Vibrio qinghaiensis test was faster and more sensitive. Meanwhile, the toxicity indicators were significantly and positively correlated with the TSS, TN, TP and COD concentrations. These results may aid the understanding of the toxicity of pharmaceutical industrial park wastewaters and toxicity removal using the treatment techniques that are currently utilized in China. Highlights: The toxicity testing methods of wastewater were established and compared. Wastewater toxicities had a significantly positive relation to TSS, TN, TP and COD. The toxicity limits of influent and effluent in a wastewater plant were calculated. The levels of toxicities and conventional indexes were reduced after most stages.